The Dream in Ingmar Bergman’s The Passion of Anna (1969) As a Reverse Journey of His Film Shame (1968) - García-Mansó, Angélica (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2021)
Anna's dream scene in Ingmar Bergman's film Passion (1969) is analysed on three levels: firstly, as an autonomous narrative; secondly, in the context of the film; and finally, in relation to Bergman's own film Shame (1968), which immediately precedes and from which the images are taken. The importance of the extradiegetic in the film, an inverse reading key to the one offered in Shame and, finally, a mythological parallelism derived from a comparative approach, are respectively inferred. At last, dream, myth and cinema manifest themselves in Bergman´s art as the three sides of a triangle on the exegesis of a film.
Keywords: Ingmar Bergman; The Passion of Anna; Shame; Film analysys; Dream; Mythology